2022
DOI: 10.3389/fphar.2022.969930
|View full text |Cite
|
Sign up to set email alerts
|

Membranous nephropathy: Systems biology-based novel mechanism and traditional Chinese medicine therapy

Abstract: Membranous nephropathy (MN) is a renal-limited non-inflammatory autoimmune disease in the glomerulus, which is the second or third main cause of end-stage kidney diseases in patients with primary glomerulonephritis. Substantial achievements have increased our understanding of the aetiology and pathogenesis of murine and human MN. The identification of nephritogenic autoantibodies against neutral endopeptidase, phospholipase A2 receptor (PLA2R) and thrombospondin type-1 domain-containing 7A (THSD7A) antigens pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 147 publications
0
15
0
Order By: Relevance
“…Renal fibrosis, characterized by tubulointerstitial fibrosis and glomerulosclerosis, is the final manifestation of chronic kidney disease, which was associated with a various molecular mechanisms such as activations of aryl hydrocarbon receptor [106][107][108][109][110], NF-κB [111,112] and Wnt/β-catenin [113][114][115] signalling pathways as well as dysbiosis of gut [116,117] and disorder of endogenous metabolite [118][119][120][121][122]. Kidney aging has been identified as a chronic process characterized by impaired renal function and structural changes in the tubular interstitium and glomerulus [123].…”
Section: Aging-related Renal Fibrosismentioning
confidence: 99%
“…Renal fibrosis, characterized by tubulointerstitial fibrosis and glomerulosclerosis, is the final manifestation of chronic kidney disease, which was associated with a various molecular mechanisms such as activations of aryl hydrocarbon receptor [106][107][108][109][110], NF-κB [111,112] and Wnt/β-catenin [113][114][115] signalling pathways as well as dysbiosis of gut [116,117] and disorder of endogenous metabolite [118][119][120][121][122]. Kidney aging has been identified as a chronic process characterized by impaired renal function and structural changes in the tubular interstitium and glomerulus [123].…”
Section: Aging-related Renal Fibrosismentioning
confidence: 99%
“…Based on the metagenomic technique, one publication has uncovered that the relative abundance of Lactobacillus vaginalis , Lactobacillus reuteri , Subdoligranulum variabile , Bacteroides vulgatus and Prevotella copri was associated with changes in serum levels of albumin, total cholesterol and triglyceride, and protein expression of intrarenal immunoglobulin G (IgG) and complement 3 (C3) in rats with passive Heymann nephritis (Wang, Yang, et al, 2022). In addition, several publications have shown microbial dysbiosis in faecal samples from IMN patients when using 16S rRNA sequence analysis (Miao, Zhang, et al, 2022). Megasphaera , Megamonas , Akkermansia , Lachnospira , Roseburia and Fusobacterium exhibited a relatively‐high abundance in healthy controls compared to IMN patients (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Boulange et al reported urine levels of significantly decreased creatinine, citrate, hippurate and phenylacetate in patients with IMN (Boulangé et al, 2019). However, few studies have reported the identification of microbial‐derived metabolites in MN (Miao, Zhang, et al, 2022) although, based on combining high‐throughput sequencing analysis and untargeted metabolomics, a previous publication has shown association between microbiota and metabolites in CKD (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of studies have shown that traditional Chinese medicines (TCMs) have been widely utilized to treat patients, and TCMs have been proved to be useful in the treatment of a number of renal diseases [ 14 19 ]. BSTL is a TCM prescription that is composed of Astragalus membranaceus (Huangqi), Rehmannia glutinosa (Dihuang), Cuscuta chinensis (Tusizi), Artemisia Anomala (Liujinu), Euonymus alatus (Guijianyu), Hirudo (Shuizhi) and Salvia Miltiorrhiza Bunge (Danshen).…”
Section: Introductionmentioning
confidence: 99%